Association of ambient air pollution and meteorological factors with primary care visits at night due to asthma attack - Yamazaki, Shin (Springer Japan, 2013)
AIM: The association of outdoor air pollution and meteorological elements with primary care visits at night due to asthma attack was studied. METHODS: A case–crossover study was conducted in a primary care clinic in Himeji City, Japan. The subjects were 956 children aged 0–14 years who visited the clinic with an asthma attack between the hours of 9 p.m. and 6 a.m. Daily concentrations of particulate matter, ozone, nitrogen dioxide, and a number of meteorological elements were measured, and a conditional logistic regression model was used to estimate odds ratios (ORs) of primary care visits per unit increment of air pollutants or meteorological elements. The analyses took into consideration the effects of seasonality. RESULTS: Of the 956 children, 73 (7.6 %) were aged <2 years and 417 (43.6 %) were aged 2–5 years. No association between daily ozone levels and primary care visits due to asthma attack at night in the spring or summer was found. An inverse relation between suspended particulate matter and primary care visits due to asthma attack was detected in the winter. ORs in the summer per degree increment in daily mean temperature was 1.31 [95 % confidential interval (CI) 1.09–1.56], and ORs in the autumn per hourly increment in daily hours of sunshine was 0.94 (95 % CI 0.90–0.99). CONCLUSION: The findings of our study fail to support any association between daily mean concentration of air pollutant and primary care visits at night. However, we did find evidence indicating that certain meteorological elements may be associated with primary care visits